The Nicomachean ethics - Aristotle (Cambridge Hackett Publishing, 1999)
The most influential ethical treatise ever written, Aristotle's Nicomachean Ethics offers accounts of human happiness and welfare; the nature of a good person; the psychology of action and character; the virtues of character and intellect; praise, blame, and moral responsibility; practical reason; weakness of will; self-interest and the interests of others; the role of friendship in the good life; and the relation between pleasure and goodness. This edition offers more aids to the reader than are found in any other modern English translation. It includes an Introduction; headings to help the reader follow the argument; explanatory notes on difficult or important passages; and a full glossary explaining Aristotle's technical terms. For this edition, the translation has been revised, and the notes and glossary expanded.
Includes bibliographical references
Keywords: Ethics